Environmental Risk Assessment of Microplastics in Water and Sediments along Ibi Troughs North-East Nigeria - Adam, Habiba Idris; Oluwale, Otitoju; Adebisi, Arowora Kayode; Umaru, Isaac John; Mohammed, Ikrimah Usman; Joseph, Iornenge Terungwa (Darul Yasin Al Sys, 2024)
This study aimed to evaluate the risk associated with microplastics along river Ibi. Water and sediment samples were collected from five (5) sites each along river Ibi 100m apart. The surface sediment was sampled in all cases to approximately 5-cm depth using a Van Veen grab (25 cm2). Microplastics particles were identified using Fourier Transform-Infrared Spectroscopy (FTIR). The FTIR spectra of the water and sediment showed bands and wave numbers of between 3275 cm-1 and 1033 cm-1 as the prominent peaks. The peaks at these frequencies were strong, broad and medium, which suggest the presence of compounds with the functional groups of alkanes, alkenes, alkynes, amines, alkyl halide, nitro compound, carbonyl bond, carboxylic acids and alcohols in the samples. The review analysis also shows that various polymer types have been covered in the studies polyethylene (PE), polypropylene (PP), polystyrene (PS), polyamide (PA), and polyethylene terephthalate (PET). Polyethylene (PE) and Polypropylene (PP) is the dominant polymer types found in all environmental matrices. Non-carcinogenic risk assessment shows hazard indices above one at every sampling location in river Ibi, indicating that drinking water from these water bodies may present serious health risks, including cardiovascular and non-carcinogenic health issues. The results obtained from this study showed that water from the sampling locations are not suitable for human consumption and also confirm the presence of microplastic in river Ibi.